High Prevalence and Frequent Acquisition of Clostridium difficile Ribotype 002 Among Nursing Home Residents in Hong Kong. (7th May 2018) - Luk, Shik; Ho, Alex Yat Man; Chan, Eliza Hoi Ying; Tsang, Iris Hoi Ling; Ng, Tak Keung; To, Wing Kin; Choi, Kin Wing; Wong, Andrew Tin Yau
Abstract : OBJECTIVE: To determine the incidence and risk factors associated with Clostridium difficile colonization among residents of nursing homes and to identify the ribotypes of circulating C. difficile strains. DESIGN: A prospective cohort study with a follow-up duration of 22 months. SETTING: Nursing homes. PARTICIPANTS: Of the 375 residents in 8 nursing homes, 300 residents (80.0%) participated in the study. A further prospective study of 4 nursing homes involving 141 residents with a minimum of 90 days of follow-up was also performed. METHODS: Baseline and 90-day stool cultures were obtained; additional stool cultures were obtained for residents who had been discharged from hospitals. Polymerase chain reaction (PCR) ribotyping and slpA typing were performed for all C. difficile strains isolated. RESULTS: Toxigenic C. difficile was isolated in 30 residents (10%) at baseline, and 9 residents (7.3%) had acquired toxigenic C. difficile in the nursing homes. The presence of nasogastric tube was an independent risk factor (adjusted odds ratio, 8.59; 95% confidence interval, 1.18–62.53; P =.034) for C. difficile colonization. The Kaplan-Meier estimate of median carriage duration was 13 weeks. The C. difficile ribotypes most commonly identified were 002 (40.8%), 014 (16.9%), 029 (9.9%), and 053 (8.5%). CONCLUSIONS: The high incidence of C. difficile colonization and the overrepresentation of C. difficile ribotype 002 confirmed the contribution of nursing home residents to C. difficile transmission across the continuum of care. An infection control program is needed in long-term care. Infect Control Hosp Epidemiol 2018;782–787